2012
DOI: 10.1016/j.amjopharm.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Analgesics Commonly Used by Older Adults With Osteoarthritis: Focus on Non-Opioid and Opioid Analgesics

Abstract: Background Osteoarthritis (OA) is the most common cause of disability in older adults, and while analgesic use can be helpful its use can also result in adverse drug events. Objective To review the recent literature to describe potential adverse drug events (ADEs) associated with analgesics commonly used by older adults with OA. Methods To identify articles for this review, a systematic search of English-language literature (January 2001 – June 2012) was conducted using PubMed, MEDLINE, EBSCO, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
162
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 59 publications
8
162
0
6
Order By: Relevance
“…It is known that current guidelines recommend the use of paracetamol as the analgesic of choice for mild to moderate pain caused by osteoarthritis of the knee and hip. 15 In patients for whom acetaminophen does not contain adequate analgesia or has little anti-inflammatory effect, NSAIDs are recommended. 38 Polypharmacy was directly linked to the use of anti-inflammatories and analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that current guidelines recommend the use of paracetamol as the analgesic of choice for mild to moderate pain caused by osteoarthritis of the knee and hip. 15 In patients for whom acetaminophen does not contain adequate analgesia or has little anti-inflammatory effect, NSAIDs are recommended. 38 Polypharmacy was directly linked to the use of anti-inflammatories and analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…10 Brazilian studies report that self-medication with analgesics is a common occurrence among the elderly, as the use of such medication is related to the treatment of pain and inflammation, common symptoms for this age group. [11][12][13] The American Geriatrics Society Panel on Persistent Pain among the Elderly 14 found that non-opioid analgesics are the most widely used drugs for pain management, although studies 12,14,15 have found an increase in the use of opioid analgesics in Europe and North America. Opioid analgesics provide an analgesia for moderate to severe pain, but should be used with caution as they can cause constipation, respiratory depression and dellirium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aunque estos fármacos son eficaces para controlar el dolor y la inflamación causados por dichas enfermedades, también generan reacciones adversas graves, entre ellas, la hemorragia digestiva, la cual encabeza la lista de causas de hospitalización por reacciones adversas a medicamentos en adultos mayores a nivel mundial. En este estudio, los antinflamatorios no esteroideos ocuparon el segundo lugar con el 12 % de dichos reportes en Bogotá (23)(24)(25).…”
Section: Discussionunclassified